Stop Blaming me for What Others Did to you: New Alternative Masculinity’s Communicative Acts Against Blaming Discourses - Schubert, Tinka; Aguilar, Consol; Kim, Kyung Hi; Gómez, Aitor (Frontiers in Psychology, 2021)
Some feminist discourses blame some men for gender inequality, gender domination and gender-based violence. Some women use such discourse as a perfect scenario to criticize some men’s behavior. Indeed, they usually do so with Oppressed Traditional Masculinities but not with Dominant Traditional Masculinities, who are the men who were violent with those women and with whom some of those women chose to have relationships. However, there have always been men who have been on the side of women and have never committed violence against them. Therefore, New Alternative Masculinities reject being indicated as guilty of the violence committed against women by Dominant Traditional Masculinities. Through a communicative approach, applying 6 semi-structured interviews with a communicative orientation and a communicative data analysis of all information, this article explores both women’s communicative acts that blame Oppressed Traditional Masculinities for what Dominant Traditional Masculinities have done to women and New Alternative Masculinities’ reactions to these accusations to stop such blaming to make it possible to overcome hegemonic discourses.